2015
DOI: 10.1089/neu.2014.3488
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Intoxication and Long-Term Outcome in Patients with Traumatic Brain Injury

Abstract: The effect of blood alcohol concentration (BAC) on outcome after traumatic brain injury (TBI) is controversial. We sought to assess the independent effect of positive BAC on long-term outcome in patients with TBI treated in the intensive care unit (ICU). We performed a retrospective analysis of 405 patients with TBI, admitted to the ICU of a large urban Level 1 trauma center between January 2009 and December 2012. Outcome was six-month mortality and unfavorable neurological outcome (defined as a Glasgow Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…Eighteen observational studies containing a total of 48,537 (37%) patients with positive BAC and 82,487 (63%) patients with negative BAC were ultimately included, and the mortality rates were analyzed in this meta‐analysis (Alexander et al., ; Berry et al., , ; Brennan et al., ; Chamoun et al., ; Chen et al., ; Gururaj, ; Hsieh et al., ; Levy et al., ; Lin et al., ; Lustenberger et al., ; Pandit et al., ; Raj et al., ; Salim et al., ,; Shandro et al., ; Tien et al., ). The overall mortality rate, the mortality rate of BAC‐positive subjects, and the mortality rate of BAC‐negative subjects, all with TBI, were 13.2%, 12.4%, and 13.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen observational studies containing a total of 48,537 (37%) patients with positive BAC and 82,487 (63%) patients with negative BAC were ultimately included, and the mortality rates were analyzed in this meta‐analysis (Alexander et al., ; Berry et al., , ; Brennan et al., ; Chamoun et al., ; Chen et al., ; Gururaj, ; Hsieh et al., ; Levy et al., ; Lin et al., ; Lustenberger et al., ; Pandit et al., ; Raj et al., ; Salim et al., ,; Shandro et al., ; Tien et al., ). The overall mortality rate, the mortality rate of BAC‐positive subjects, and the mortality rate of BAC‐negative subjects, all with TBI, were 13.2%, 12.4%, and 13.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the first study [65], 405 patients were retrospectively grouped according to blood alcohol concentration (BAC) on hospital admission after TBI: no BAC ( n = 99), low BAC (<2.3 %, n = 140), and high BAC (>2.3 %, n = 166). The primary outcome measures included 6-month mortality and unfavorable neurological outcome (GOS 1–3).…”
Section: Pharmacological Agents With Mixed Results After Tbimentioning
confidence: 99%
“…18,31,34 However, a recent study found low BAC levels also to significantly decrease risk of 6-month mortality. 36 Third, we could not assess the effect of different levels of BAC on outcome.…”
Section: Limitationsmentioning
confidence: 99%